Hip-Preserved Reconstruction Using a Customized Cementless Intercalary Endoprosthesis With an Intra-Neck Curved Stem in Patients With an Ultrashort Proximal Femur: Midterm Follow-Up Outcomes - You, Qi; Lu, Minxun; Min, Li; Zhang, Yuqi; Wang, Jie; Wang, Yitian; Zheng, Chuanxi; Zhou, Yong; Tu, Chongqi (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Hemiarthroplasty is widely used for proximal femoral reconstruction after tumor resection. However, complications of hemiarthroplasty include infection, hip dislocation, and acetabular wear. This study aimed to:(1) evaluate the reliability and validity of a customized cementless intercalary endoprosthesis (CCIE) with an intra-neck curved stem (INCS) to reconstruct femoral diaphyseal defects with an ultrashort proximal femur (UPF); (2) assess the lower extremity function after reconstruction with this endoprosthesis; and (3) identify the postoperative complications associated with the use of this endoprosthesis. Methods: Between October 2015 and May 2019, 13 patients underwent reconstruction with a CCIE with an INCS. The distance from the center of the femoral head to the midline of the body and the apex of the acetabulum was measured preoperatively. Additionally, the distance from the tip of the INCS to the midline of the body and the apex of the acetabulum was measured postoperatively. The femoral neck–shaft angle was also measured pre- and postoperatively. After an average follow-up duration of 46 months, the radiological outcomes of the CCIE with an INCS were analyzed. Function was evaluated with the Musculoskeletal Tumor Society (MSTS) score. Pain was measured using a paper visual analog scale (VAS) pre- and postoperatively, and complications were recorded. Results: Compared with our preoperative design, we found no significant difference in the postoperative distance from the tip of the INCS to the body midline (P = 0.187) and the apex of the acetabulum (P =0.159), or in the postoperative femoral neck–shaft angle (P = 0.793). Thus, the INCS positions were deemed accurate. The average MSTS score was 26 (range: 24–28), and the VAS score was significantly decreased postoperatively compared with preoperatively (P < 0.0001). No patients developed aseptic loosening, infection, periprosthetic fracture, or prosthetic fracture as of the last follow-up. Conclusion: The CCIE with an INCS was a valid and reliable method for reconstructing femoral diaphyseal defects with a UPF following malignant tumor resection. Postoperative lower extremity function was acceptable, with an appropriate individualized rehabilitation program, and the incidence of complications was low.